X-Chromosome Inactivation Analysis in Different Cell Types and Induced Pluripotent Stem Cells Elucidates the Disease Mechanism in a Rare Case of Mucopolysaccharidosis Type II in a Female - Řeboun, M; Rybová, J; Dobrovolný, R; Včelák, J; Veselková, T; Štorkánová, G; Mušálková, D; Hřebíček, M; Ledvinová, J; Magner, M; Zeman, J; Pešková, K; et al. (Folia biologica, 2016)
Mucopolysaccharidosis type II (MPS II) is an X-linked lysosomal storage disorder resulting from deficiency of iduronate-2-sulphatase activity. The disease manifests almost exclusively in males; only 16 symptomatic heterozygote girls have been reported so far. We describe the results of X-chromosome inactivation analysis in a 5-year-old girl with clinically severe disease and heterozygous mutation p.Arg468Gln in the IDS gene. X inactivation analysed at three X-chromosome loci showed extreme skewing (96/4 to 99/1) in two patient's cell types. This finding correlated with exclusive expression of the mutated allele. Induced pluripotent stem cells (iPSC) generated from the patient's peripheral blood demonstrated characteristic pluripotency markers, deficiency of enzyme activity, and mutation in the IDS gene. These cells were capable of differentiation into other cell types (cardiomyocytes, neurons). In MPS II iPSC clones, the X inactivation ratio remained highly skewed in culture conditions that led to partial X inactivation reset in Fabry disease iPSC clones. Our data, in accordance with the literature, suggest that extremely skewed X inactivation favouring the mutated allele is a crucial condition for manifestation of MPS II in females. This suggests that the X inactivation status and enzyme activity have a prognostic value and should be used to evaluate MPS II in females. For the first time, we show generation of iPSC from a symptomatic MPS II female patient that can serve as a cellular model for further research of the pathogenesis and treatment of this disease.
Keywords: mutace; Female; iduronátsulfatasa; předškolní dítě; Induced Pluripotent Stem Cells; mukopolysacharidóza II; ženské pohlaví; lidé; indukované pluripotentní kmenové buňky; Iduronate Sulfatase; Mutation; kultivované buňky; Cells, Cultured; Male; Child, Preschool; Mucopolysaccharidosis II; X Chromosome Inactivation; inaktivace chromozomu X; mužské pohlaví; Humans